2012
DOI: 10.1097/qai.0b013e31823b4448
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of the Kenya Postelection Crisis on Clinic Attendance and Medication Adherence for HIV-Infected Children in Western Kenya

Abstract: HIV-infected children are at risk for disruptions in clinic follow-up and medication adherence after a humanitarian crisis. Individual and contextual factors moderate the effects of these disruptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…[55,56] Interruptions in antiretroviral treatment, promoted by political crisis or conflicts in sub-Saharan Africa, may lead to unplanned treatment interruptions due to medical supplies disruption, displacement of the population, unsafe travel, limited access to health care, and incapability to obtain medications, and may be associated with worsening HIV infection [57] as well as with virological failure. [58] Children are particularly vulnerable in crises and are at increased risk of abandonment, abduction, malnutrition, and communicable diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[55,56] Interruptions in antiretroviral treatment, promoted by political crisis or conflicts in sub-Saharan Africa, may lead to unplanned treatment interruptions due to medical supplies disruption, displacement of the population, unsafe travel, limited access to health care, and incapability to obtain medications, and may be associated with worsening HIV infection [57] as well as with virological failure. [58] Children are particularly vulnerable in crises and are at increased risk of abandonment, abduction, malnutrition, and communicable diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[58] Children are particularly vulnerable in crises and are at increased risk of abandonment, abduction, malnutrition, and communicable diseases. [56] Studies on the impact of the political and humanitarian crisis after the contested 2007 Kenyan presidential election showed small but statistically significant disruptions in clinical care and medication adherence among children on antiretroviral treatment despite a comprehensive health care response. [56,59,60] The Central African Republic was suffering during the study period from a major and out of control health and humanitarian crisis [44,61,62] which affected particularly the HIV epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…34 Although this crisis was associated with treatment interruptions for HIV-infected children enrolled in Western Kenya, 35 several factors were reported that may have minimized disruptions in clinical care, including an established network of health facilities, resilient supply chain systems for food and medicines, dedicated community health workers, radio and print communication campaigns, and electronic medical records systems. 36 …”
Section: Figurementioning
confidence: 99%
“…Several anecdotal reports have speculated on the likelihood of negative effects of the epidemic on established treatment programs (such as for malaria [8]), leading in turn to a probable rise in non-Ebola related health problems [9]. Previous reports have documented the impact of man-made threats on HIV care [10, 11]. The present epidemic is an opportunity to look at the impact of a major threat of natural origin on HIV care [12].…”
Section: Introductionmentioning
confidence: 99%